Coping with Biographical and Identity Crises across Different Profiles of Personal Time Perspective in Extreme Living Conditions - E. M. Meshcheryakova (СибСкрипт)
Experiences related to normative and non-normative developmental crises reduce adaptability and self-regulation, making crisis coping studies a relevant research topic. Personal time perspective is a personality resource that defines the coping strategy. Coping with biographical or identity crises remains understudied in the context of time perspective, most publications focusing on specific temporal orientations and their correlation with crisis manifestations. This article describes the specifics of coping with biographical and identity crises across different profiles of time perspective through the prism of the temporal orientation system. The author studied the effect of time perspective profile on the intensity and nature of crisis experience and coping. The study relied on a relatively small sample of 101 residents of the Kamchatka Region with its extreme living conditions. The respondents were clustered by time perspective profile to compare the intensity of experiencing biographical crises and the spheres of crisis situations that contribute to coping with the identity crisis. A strong orientation toward the positive past proved to be the most resourceful profile of time perspective for people living in extreme climate. The respondents oriented toward the future or hedonistic present appeared to be less adaptive to crisis states. Those oriented toward a fatalistic present and a negative past demonstrated the greatest risk. However, the time perspective profile did not guarantee an identity crisis, but only increased the risks and changed the emphasis.